Wrongful convictions of women : when innocence isn't enough - Free, Marvin D.
Marvin Free and Mitch Ruesink reveal the distinctive role that gender dynamics so often play in the miscarriage of justice. Examining more than 160 cases involving such charges as homicide, child abuse, and drug trafficking, the authors explore systemic failures in both policing and prosecution. They also highlight the intersecting roles of gender and race. Demonstrating how women encounter circumstances that are qualitatively different than those of men, they illuminate unique challenges facing women in the criminal justice system.